Reducing Delays to Antiretroviral (ARV) Receipt in Children Prescribed Post-Exposure Prophylaxis (PEP) for HIV: Meds-in-Hand and a Multidisciplinary Team Approach. (4th October 2017) - Epstein, Rachel; Penwill, Nicole; Clarke, Diana; Hamilton, Sebastian; Moses, James; Cooper, Ellen
Abstract: Background: Provision of antiretrovirals (ARVs) for pediatric patients who require HIV post-exposure prophylaxis (PEP) poses many challenges. Many pharmacies do not stock pediatric formulations of ARVs. Prior authorizations and misunderstanding of medication quantity and urgency can delay filling and result in treatment interruptions, risking PEP's efficacy. While 3-day starter packs are standard of care for patients prescribed PEP in the Emergency Department (ED), we are not aware of programs designed to ensure pediatric patients receive the full 28-day course. Methods: At Boston Medical Center using the Model for Improvement with Plan-Do-Study-Act (PDSA) cycles, we implemented three key interventions: 1) Initiation of "Meds-in-Hand" for patients prescribed PEP during outpatient pharmacy business hours in which the entire course of ARVs is dispensed and handed to the patient in the ED; 2) Establishment of a troubleshooting PEP group email chain for medication receipt after a starter pack is given; and 3) Creation of an ED-Pharmacy workflow to help providers avoid logistic prescription errors. Using run charts, we tracked the proportion of patients who received Meds-In-Hand or a 3-day starter pack over time, and identified delays in full PEP course receipt. Results: Of the 29 courses of HIV PEP prescribed from our Pediatric ED during 2016, with mean age 16 years (range 1–22 years), the proportion of patients with delays in prescription pick-up that would result in gaps in therapy decreased from 45% (5/11) to 6% (1/18) during the intervention period (Figure 1). During 2 of 5 pre-intervention months, one patient left the ED without a starter pack; all patients in the invention period left with either a starter pack or Meds-In-Hand. Of patients seen during pharmacy business hours, 50% (2/4) during PDSA cycle 2 and 100% (3/3) during cycle 3 received the full 28-day medication course before leaving the ED. Conclusion: Patient care measures improved with a multi-disciplinary team approach involving pharmacy, pediatric infectious diseases, and ED improvements in communication and coordination of care. This quality improvement initiative demonstrates simple collaborative interventions to reduce critical delays in HIV prevention for a vulnerable population. Disclosures: All authors: No reported disclosures.